Trichomes and Allelochemicals in Tomato Genotypes Have Antagonistic Effects Upon Behavior and Biology of Tetranychus urticae - de Oliveira, João R. F.; de Resende, Juliano T. V.; Maluf, Wilson R.; Lucini, Tiago; de Lima Filho, Renato B.; de Lima, Isabela P.; Nardi, Cristiane (Frontiers in Plant Science, 2018)
Tomato genotypes selected for their high foliar zingiberene (ZGB) contents in a segregating F2 population were assessed to determine their effect on behavior and biology of Tetranychus urticae Koch, the putative resistance mechanisms involved and the role of trichomes on that resistance. Genotypes with contrasting ZGB content (RVTZ-09 = low ZGB, RVTZ-79 = high ZGB, RVTZ-142 = high ZGB, and RVTZ-331 = high ZGB) were selected from an interspecific cross between wild S. habrochaites var. hirsutum accession PI-127826 (high ZGB content and resistant to mites) and S. lycopersicum cv. Redenção (low ZGB content and susceptible to mites). To determine the effect of these genotypes on mite behavior and biology, free- and no-choice tests, as well as biological studies were performed. Types and densities of trichomes on the foliar surface and their correlation with ZGB contents was determined. Genotypes rich in ZGB (RVTZ-79, RVTZ-142, and RVTZ-331) presented a high number of types IV and VI glandular trichomes, and both type IV and VI densities were positively correlated with ZGB content. In the free-choice test, T. urticae showed a high preference toward S. lycopersicum cv. Redenção and the genotype RVTZ-09 (low ZGB content), whereas, genotypes with high ZBG content were less preferred. Moreover, on high ZGB genotypes, increase in the egg incubation period and in total mortality of nymphs, and decrease of fecundity rate were observed, indicating deleterious effects in mite biology. Results indicated that high ZGB/high glandular trichome densities genotypes present both non-preference and antibiosis mechanisms of resistance to the mite.